The rewritten expression is 6⁴
Using the rule of logarithm ;
![a^(m) ÷ a^(n) = a^(m-n)](https://img.qammunity.org/2023/formulas/mathematics/high-school/q8wpx6x8vt3tqsbr5447z0cis2whm4zqrf.png)
The expression given is ;
The exponent of the numerator = 5
The exponent of the denominator = 1
Subtract the exponents since they have the same base
exponent = 5 - 1 = 4
6⁵/6 =
![6^(5) ÷ 6^(1) = a^(5 - 1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/u8emlp465dom6stuk9kdd4lmbkuv14pgo1.png)
Hence , the expression is 6⁴